CURRENCY COMPETITION AND ITS CONSEQUENCES - Marszałek, Paweł (Ekonomia i Prawo. Economics and Law, 2010)
The aim of the paper is to present processes of currency competition in the contemporary economics. The problem is of special importance, because such a competition has recently intensified to a large degree, mainly due to significant changes in monetary systems around the world. Moreover, currency competition is multidimensional process that brings serious consequences for states, their citizens and central banks as well. In the second point definitions of currency competition are presented, as well as its features and dimensions. The third point characterizes the most controversial area of currency competition, namely rivalry between public and private monies, whereas the fourth one – chosen consequences of competition between different monetary units.